Creative Ways of Demonstrating Your Value Using a Library Dashboard - ECLEVIA, MARIAN RAMOS; Vinzon, Minette R.; Balbas, Yugosto A.; Janio, Rizalyn V. (Qualitative and Quantitative Methods in Libraries, 2019)
The study primarily aims to explore visualisation approaches used by libraries in visualising analytics to present their value and impact on the academic community. It attempts to investigate and answer the following research questions: (1) What are the current practices of academic libraries in data sharing and visualisation?; (2) What kinds of data are displayed on library websites and dashboards?; and, (3) How do libraries visualise their data on the web? This study is a descriptive survey research design that employed content analysis to examine the library websites of the top 500 universities based on QS World University Ranking 2018 and ascertain the presence of public-facing data and availability of library dashboards. Website investigation and capturing of web pages were conducted from September 2018 to March 2019. A total of 157 universities published their library data on the web. Many libraries of top-ranking universities published their data online using textual facts and figures. Surprisingly, data show that only a few academic libraries around the world have developed their data dashboards. It implies that librarians have not taken full advantage of the benefits of data visualisation. Library data in dashboards are presented in a visually less appealing and interactive report using visualisation tools that delivers clear insights to library patrons, university administrators, and accrediting agencies. Published library data include reference transactions, usage of services, collections and spaces, library visits (physical and virtual), numbers of eBooks, online journals, open access resources and other collections, interlibrary and document delivery transactions, staffing, budget and expenditures, items checked out, library instruction sessions and attendees, equipment loans, digital image documents, new acquisition, and digitisation. Most data are text, numbers, and graphs, thus, not-interactive and real-time. The results of this study may prescribe best practices in communicating library data to its stakeholders, in which Filipino librarians may benchmark. Librarians can make better, more data-driven decisions to drive continuous improvement of library operations.